2019
DOI: 10.1109/access.2019.2895904
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Unpackaged 60 GHz Planar Antenna Array

Abstract: A high gain antenna array is designed and fabricated at 60 GHz. The array is via-less and made on a single dielectric substrate. It can be easily integrated with millimeter wave transceivers. Very good agreement between the measured and simulated results is achieved. The array has 22.5 dBi gain with a maximum efficiency of 93% and a 3.2 % bandwidth. INDEX TERMS High gain antenna array, millimeter-wave antenna array, low profile antenna, planar antenna.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…At higher frequencies, the gain of the antenna is essential to compensate for the path loss; there are several ways and various structures that can be used to achieve high gain performance metric 50 . Reflectors, and lenses are well known for their ability to provide high gain 51 .…”
Section: Utilizing Microstrip Line Discontinuities To Implement Effic...mentioning
confidence: 99%
See 3 more Smart Citations
“…At higher frequencies, the gain of the antenna is essential to compensate for the path loss; there are several ways and various structures that can be used to achieve high gain performance metric 50 . Reflectors, and lenses are well known for their ability to provide high gain 51 .…”
Section: Utilizing Microstrip Line Discontinuities To Implement Effic...mentioning
confidence: 99%
“…In Ref. 50 we showed that such a printed open microstrip line stub can be used as a radiating element where the radiation from the fringing fields can be utilized. As in Fig.…”
Section: Utilizing Microstrip Line Discontinuities To Implement Effic...mentioning
confidence: 99%
See 2 more Smart Citations
“…By increasing the number of stubs, a significant electrical aperture area can be obtained and can produce significant directivity in the boresight. Further details about the radiation mechanism can be found in [12]- [15].…”
Section: Proposed Printed Feedmentioning
confidence: 99%